Exploring Hope and Future Orientation in Adolescents from Low-Income Communities - Karna, Wioleta; Ahmmed, Badhon; Hakobyan, Anahit (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to explore how adolescents from low-income communities in Pakistan perceive and construct hope and future orientation. Methods and Materials: The study employed a qualitative design using semi-structured interviews with 20 adolescents aged 14 to 18 years from low-income urban and semi-urban communities in Pakistan. Participants were selected through purposive sampling to ensure diversity in gender and educational status. Data were collected until theoretical saturation was reached. All interviews were conducted in Urdu, transcribed verbatim, and analyzed thematically using NVivo software. Thematic analysis followed Braun and Clarke’s six-step approach, focusing on identifying patterns related to hope, aspirations, coping mechanisms, and environmental influences. Findings: Thematic analysis revealed four major categories: hope as a psychological resource, barriers to future orientation, future goals and aspirations, and sources of hope and support. Subcategories within these themes included emotional resilience, self-efficacy, spiritual coping, family responsibilities, economic hardship, gender constraints, educational dreams, altruistic goals, and community-based support systems. Adolescents expressed strong internal motivation and aspirational thinking despite significant socio-economic barriers. Support from parents, peers, teachers, and religious beliefs played a key role in sustaining their hope. However, structural challenges such as poverty, school quality, and restrictive gender norms frequently disrupted their goal pursuit. Conclusion: Despite living in disadvantaged conditions, adolescents from low-income communities in Pakistan demonstrate meaningful hope and future orientation. Strengthening psychosocial supports, enhancing educational resources, and addressing structural inequities are essential for nurturing their developmental potential.